تفسیر قرآن کا سائنسی رحجان موافق و مخالف نظریات کا تقابلی جائزہ : Scientific Trends in Qur’anic Exegesis: A Comparative Study of Supporting and Opposing Perspectives (Al-NASR, 2024)
The relationship between the Qurʾān and modern science has remained a sensitive and intellectually contested subject within the field of Qur’anic exegesis. With the rapid advancement of scientific knowledge in the modern era, a distinct interpretive trend emerged that seeks to harmonize certain Qur’anic verses with contemporary scientific theories and discoveries. This approach, commonly referred to as scientific exegesis of the Qurʾān, has attracted both strong support and serious criticism among Muslim scholars.This study presents a critical and comparative analysis of the scientific trend in Qur’anic interpretation by examining the arguments of both its proponents and opponents. Through a detailed review of classical and modern exegetical works, the research evaluates the methodological foundations, objectives, and limitations of scientific interpretation. Particular attention is given to prominent scholars who advocated scientific harmony, as well as those who cautioned against imposing mutable scientific theories upon immutable divine revelation. The study argues that while the Qurʾān encourages reflection upon the natural world, its primary purpose remains moral guidance and spiritual reform rather than scientific instruction. The paper concludes that a balanced and disciplined approach is essential to avoid exaggeration, forced interpretation, and intellectual inconsistency in relating the Qurʾān to modern science.
Keywords: Scientific Exegesis of the Qurʾān; Qurʾān and Science; Tafsīr Studies; Modern Interpretive Trends; Islamic Thought; Scientific Miracles of the Qurʾān; Limits of Interpretation; Religion and Science; Qur’anic Studies; Islamic Ethics; Comparative Religion